Effect of annealing, thickness ratio and bend angle on springback of AA6061-T6 with nonuniform thickness section - Adnan, M.F.; Abdullah, A.B.; Samad, Zahurin (EDP Sciences, 2017)
Non-uniform thickness section section is considered one of the most effective approaches to reduce automotive part weight. Reduction in term of mass and size result in less fuel consumption and greenhouse gases. Thickness is the most significant parameter to formability, therefore forming a section with non-uniform thickness becomes a great challenge. Improper process and incorrect decision may lead to severe defect and one of the main concerns is the springback. This study will focus on springback behaviour of non-uniform thickness AA6061 strip with complex profile using Taguchi Method. Profile projector (PC 3000) is used to measure the spring back and two-line technique is applied to measure angles (after loading) between two lines. Three parameters (i.e. annealing temperature, thickness ratio and bend angle) are studied, and results determine that the most significant parameter is bend angle, followed by thickness ratio, and then by the annealing temperature of the specimen during bending process.